Model Predict, Observe and Explain Pembelajaran Muatan IPS Kelas IV di SDN Pondok Bambu 06 Jakarta - Ajat Sudrajat; Dudung Amir Soleh; Winda Dewi Lityasari; Vina Iasha (UM Purwokerto Press, 2021)
The background of the research is the fact that learning outcomes are still below the KKM on social studies content, namely 80%. Researchers used Predict, Observe and Explain models in improving SD social studies learning outcomes. The research model design was classroom action research which was adapted from the model of Kemmis and Mc.Taggart. The tools used to collect data in this study were student and teacher observation data to see the application of the Predict, Observe and Explain models and evaluation sheets in measuring the improvement of learning outcomes. The research achievement can be seen from the application of the Predict, Observe and Explain model stages to students and teachers which exceed 90% and the percentage of learning outcomes exceeds 80%. Discussion, learning outcomes in cycle I is 52%, cycle II is 65% and cycle III is 100%. Student observations in the first cycle were 60%, the second cycle was 74, the third cycle was 92. Meanwhile, the teacher's observation in cycle I is 70, cycle II is 78, and cycle III is 96. It is concluded that the Predict, Observe and Explain model is very effective for teachers to increase their creative innovation abilities and can improve learning outcomes, especially in grade IV SD social studies content. In cycle I there are still weaknesses of students who have not adapted to the learning carried out by the teacher. The teacher still hasn't done all the steps from the Predict, Observe and Explain model so that it needs to be corrected in the second cycle. In the second cycle students were able to adapt to the learning model carried out by the teacher. The teacher has started to master the Predict, Observe and Explain model but has not reached the target so it needs improvement for the third cycle. from the third cycle student learning outcomes as well as student monitoring actions and teacher monitoring actions using the Predict, Observe, and Explain models are as expected. It can be said that the Predict, Observe, and Explain models are alternative models used in elementary schools.